On the Time Evolution of Climate Sensitivity and Future Warming. Issue 9 (26th September 2018) - Goodwin, Philip
Abstract: The Earth's climate sensitivity to radiative forcing remains a key source of uncertainty in future warming projections. There is a growing realization in recent literature that research must go beyond an equilibrium and CO2 ‐only viewpoint, toward considering how climate sensitivity will evolve over time in response to anthropogenic and natural radiative forcing from multiple sources. Here the transient behavior of climate sensitivity is explored using a modified energy balance model, in which multiple climate feedbacks evolve independently over time to multiple sources of radiative forcing, combined with constraints from observations and from the Climate Model Intercomparison Project phase 5 (CMIP5). First, a large initial ensemble of 10 7 simulations is generated, with a distribution of climate feedback strengths from subannual to 10 2 ‐year timescales constrained by the CMIP5 ensemble, including the Planck feedback, the combined water vapor lapse rate feedback, snow and sea ice albedo feedback, fast cloud feedbacks, and the cloud response to sea surface temperature adjustment feedback. These 10 7 simulations are then tested against observational metrics representing decadal trends in warming, heat and carbon uptake, leaving only 4.6 × 10 3 history‐matched simulations consistent with both the CMIP5 ensemble and historical observations. The results reveal an annual timescale climate sensitivity of 2.1 °C (ranging from 1.6 to 2.8 °C at 95% uncertainty), rising to 2.9 °C (from 1.9 to 4.6 °C) on century timescales. These findings provide a link between lower estimates of climate sensitivity, based on the current transient state of the climate system, and higher estimates based on long‐term behavior of complex models and palaeoclimate evidence. Plain Language Summary: The Earth's climate sensitivity is a measure of how much the average surface temperature will increase if atmospheric carbon dioxide levels are doubled. There is currently a wide variation in estimates of the Earth's climate sensitivity at equilibrium, from low estimates around 1.5 °C to high estimates around 4.5 °C. Many different climate processes affect the value of the climate sensitivity, for example the responses to surface warming of clouds, atmospheric water vapor, and changes in the reflectivity of Earth's surface as snow and ice melt. These processes occur on different timescales, for example it takes days for water vapor to change in the atmosphere, but much longer to melt a large ice sheet. This study applies a range of observational constraints to climate model simulations in order to constrain the Earth's climate sensitivity, considering how the climate sensitivity varies on different timescales. A best estimate for climate sensitivity is found to be 2.1 °C (with uncertainty ranging from 1.6 to 2.8 °C) over yearly timescales. However, climate sensitivity increases to 2.9 °C (ranging from 1.9 to 4.6 °C) on century timescales, affecting future anthropogenic warming. Key Points: The climate sensitivity response varies with response timescale The climate sensitivity response on annual timescales is 2.1 °C, and between 1.6 and 2.8 ° at 95% uncertainty The climate sensitivity response on century timescales is 2.9 °C and between 1.9 and 4.6 ° at 95% uncertainty